Efficiency Evaluation and Spatio-Temporal Differentiation Analysis of tourism Industry in Cities Along the Beijing Hangzhou Grand Canal Based on Three-Stage DEA - Xin Zhang; ShiFeng Wu (SAGE Open)
The Beijing Hangzhou Grand Canal has become an important component of China’s national cultural park construction. In order to improve the tourism efficiency of cities along the Beijing Hangzhou Grand Canal, this paper constructs an evaluation index system for tourism efficiency of cities along the Beijing Hangzhou Grand Canal based on spatial production theory. The three-stage DEA model are used to evaluate the tourism efficiency of 22 cities along the Beijing Hangzhou Grand Canal in 2015, 2017, and 2019, and analyze the spatiotemporal differences in tourism efficiency. Research has found that firstly, the development of tourism in Beijing, Tianjin, Tai’an, Zhenjiang, Huzhou, and Hangzhou is efficient. The comprehensive tourism efficiency of Xingtai, Zaozhuang, Suqian, and Huai’an is greatly affected by scale efficiency, while the comprehensive tourism efficiency of Xuzhou and Changzhou is more affected by pure technical efficiency. The tourism efficiency of other cities is influenced by the alternating effects of two decomposition efficiencies. Secondly, “tourism dependence” and “actual utilization of foreign investment” have a positive effect on promoting the overall efficiency and scale efficiency of tourism, but are not conducive to the improvement of pure technological efficiency. Thirdly, the global spatial autocorrelation characteristics of tourism efficiency in cities along the Beijing Hangzhou Grand Canal are not significant. Locally developed tourism areas exhibit “H-H” characteristics, while underdeveloped tourism areas exhibit “H-L” and “L-L” distribution characteristics. The findings of this study can provide reference for the development of tourism resources in cities along the Beijing Hangzhou Grand Cana.